Bullying in the workplace: a case study of the University of Cape Town - Phillips, Patricia (Department of Private Law, 2025)
Workplace bullying likely started after the Industrial Revolution, with the development of formal workplaces like factories and offices, and has increasingly become a problem in workplaces, particularly for victims on whom the impact can be lifelong and debilitating. This minor dissertation explores global and South African prevalence to demonstrate the extent of this harmful practice. It further reviews global and South African legislation and introduces bullying in academia as a backdrop to the Case Study on Bullying at the University of Cape Town. While research on workplace bullying had primarily focussed on the personality traits of victims and perpetrators, this minor dissertation attempts to draw on themes drawn from a review of Criminological Theory (Routine Activities and Normalisation Theory) and Transformational Theory to present a case study on Bullying at the University of Cape Town. These themes include the normalisation of deviant behaviour in workplaces, the impact of guardians failing employees in their protective role in organisations, the impact of life-changing events on both the individual and the organisation, and finally, how dysfunctional organisational structure contributes to workplace bullying with particular reference to the University of Cape Town. Finally, it explores whether workplace bullying can be addressed by legislation and implementation of workplace policies.